Influence of Different Feeding Ratio of Pomegranate Peels Powder on Testicular Dimensions, Body Weight and Testosterone Concentration in Karadi Male Lambs - Karzan A. Ahmed; Dereen O. Muhammed; Sarwar M. Sadq (مجلة الانبار للعلوم البيطرية, 2019)
The current study was presented to conclude the influence of different ratio of pomegranate peel powder (PP) in feed of Karadi male lambs, they divided to 4 groups (0% as a control, 1% treatment 1, 2% treatment 2 and 4% as treatment 3), on scrotal circumference (SC), scrotum height (SH), body weight (BW) and blood serum testosterone concentration (T). In this study, sixteen (16) of Karadi male lambs used with 24.30 ± 0.40 kg weight and with 4-5 months old, all lambs have been randomly divided equally into four (4) groups and individually penned in a box for during 63 days. Results in our study showed that SC was significantly different and recorded higher 17.875±0.54 cm in group that fed on 1% PP, also SH recorded higher and significant different in group fed on 1% PP compared with other groups 10.000±0.32 cm. Average blood serum testosterone reduces in all groups compared to control group that fed on 0% of PP (11.418±0.15 n.mol/L). Final body weight in our study had significantly different (P < 0.05) between groups, 1% PP recorded higher weight (34.9 ± 0.58) kg. Each average daily gain, total body gain and initial body weight had not significant different in all groups. Correlation coefficient between SC, SH, blood serum testosterone concentration and final BW computed and ranged between (-0.397 to + 0.914).